Teachers' Efforts to Overcome Barriers to Students' Affective Assessment in History Learning at SMA Negeri 2 Batang - Rismawati, Lisa; Soeharso, R (Universitas Negeri Semarang, 2016)
The objectives of this study: (1) Knowing the implementation of the assessment of the affective aspects of students in teaching history in the classroom. (2) Knowing the barriers the teacher faces in assessing students' affective aspects at SMA N 2 Batang. (3) Analyzing the teacher's efforts to overcome history learning barriers in assessing the affective aspects of students at SMA N 2 Batang. The results of this study indicate that in the process of applying the student's attitude values, the teacher found several barriers that occurred in the process of learning history. In accordance with the objectives of the 2013 curriculum, which focuses on student affective assessment, this assessment is still experiencing barriers in the assessment process, which is based on the background of the teacher and students. The assessment of the affective aspects of students is carried out by means of observations, journals, self-assessment, or among friends. To overcome these barriers, the teacher made several efforts, including that every teacher had tried their best to give the best to students. In addition, teachers conduct evaluations to continue improving their performance in conducting effective assessments; everything is prepared optimally to run smoothly.